Integrated intraoperative ocular coherence tomography for pediatric ocular surgery - Nischal, Ken K. (Developments in ophthalmology / series editor F. Bandello, 2021)
Integrated or microscope-integrated intraoperative ocular coherence tomography (i2OCT or mi-OCT, respectively) has revolutionized real-time augmentation of the surgical operating field. While corneal and retinal specialists have immediately found uses for this technology, others are beginning to use it to improve outcomes and flatten the learning curve. This book presents the use of i2OCT in pediatric ocular surgery. Case scenarios in pediatric retinal disease, corneal lamellar keratoplasty, and even pediatric cataract surgery are discussed. More novel applications highlighted include its use to identify the levator muscle in oculoplastic surgery, especially re-operations, and to assess the results of glaucoma drainage devices. Identifying extraocular muscles in re-operation for strabismus ensures minimal tissue disruption during surgery. Complex pediatric cataract surgeries can be performed far more simply and effectively using integrated ocular coherence tomography technology. This volume provides invaluable information to both early career and experienced pediatric ocular specialists, as well as any researchers who are likely to encounter i2OCT or mi-OCT technology in the future.